Two new dottyback species of the genus Pseudochromis from southern Indonesia (Teleostei: Pseudochromidae) - Gill, Anthony C.; Allen, Gerald R.; Erdmann, Mark (Zootaxa, 2012)
Pseudochromis oligochrysus new species is described from nine specimens collected from Nusa Penida (off Bali) and PuraIsland (between Pantar and Alor), Indonesia. It resembles P. flavopunctatus Gill & Randall from Komodo, Indonesia, butdiffers in live coloration and scale counts. Pseudochromis rutilus new species is described from the holotype collected from Nusa Penida. It differs from similar species in being deeper bodied and in its distinctive live coloration.